MAKING LUDO WORD GAME (LWG) TO LEARN GRAMMAR FOR SENIOR HIGH SCHOOL STUDENTS - Novalina Simbolon; Ari Satria (Politeknik Negeri Bengkalis, 2016)
Abstract: English Grammar is the rules how to make a sentence in learning English. English Grammar is the important part in English, but learning Grammar is not easy especially for student Senior High School. It is because grammar has many formulas to be memorized. There are various ways in learning English that can help the students in learning English Grammar. One of the most popular and effective ways is by using games. There are many types of games that can be used as learning method and media, either electronic or conventional. One of the games is Ludo Word Game. In this study, the research question was â€œIs there a Ludo Word Game to learn grammar for senior high school students?.Â The objective of this study was to make a Ludo Word to learn grammar for senior high school students. The method of the study used was descriptive research. The result of this study was a set of Ludo Word Game that was modified with question cards. In addition, this game can help the students in learning English and can be a medium for the teacher in teaching English especially grammar.Â Keywords: Grammar, Game, Ludo Word Game